Potential growth in Central America and the Dominican Republic: Was there a pre-pandemic new normal? (2021)
This paper explores the potential growth of Central America and the Dominican Republic after the 2008-2009 crisis to shed light on their 2020 pre-pandemic macroeconomic vulnerability and to ascertain that the observed path is deviating more than before from its potential. Using Hodrick-Prescott filter by constrained minimization, production function, regime-switching models, and Bayesian model averaging, the main findings suggest a pre-pandemic regional slowdown. By country, there are mixed results. This scenario was not only driven by international factors but by particularities; on the one hand, statistical models show higher potential growth, and, in a less favorable context, the region would be closer to the structural performance; on the other hand, individual factors are hindering potential growth.